Effects of power reserve control on wind turbine structural loading. Issue 3 (25th March 2015) - Fleming, Paul A.; Aho, Jacob; Buckspan, Andrew; Ela, Erik; Zhang, Yingchen; Gevorgian, Vahan; Scholbrock, Andrew; Pao, Lucy; Damiani, Rick
Abstract: As the penetration of wind energy in worldwide electrical utility grids increases, there is a growing interest in the provision of active power control (APC) services from wind turbines and power plants to aid in maintaining grid stability. Recent research has focused on the design of active power controllers for wind turbines that can provide a range of APC services including inertial, primary frequency and secondary frequency control. An important consideration for implementing these controllers in practice is assessing their impact on the lifetime of wind turbine components. In this paper, the impact on the structural loads of a wind turbine providing a power reserve is explored by performing a load suite analysis for several torque‐based control strategies. Power reserve is required for providing those APC services that require the ability of the wind turbine to supply an increase in power. To study this, we performed a load suite on a simulated model of a research turbine located at the National Wind Technology Center at the National Renewable Energy Laboratory. Analysis of the results explores the effect of the different reserve strategies on turbine loading. In addition, field‐test data from the turbine itself are presented to augment and support the findings from the simulation study results. Results indicate that all power‐reserve strategies tend to decrease extreme loads and increase pitch actuation. Fatigue loads tend to be reduced in faster winds and increased in slower winds, but are dependent on reserve‐controller design. Copyright © 2015 John Wiley & Sons, Ltd.